Pre‐registration is a Game Changer. But, Like Random Assignment, it is Neither Necessary Nor Sufficient for Credible Science. Issue 1 (15th February 2021) - Simmons, Joseph P.; Nelson, Leif D.; Simonsohn, Uri
Abstract : We identify 15 claims Pham and Oh (2020) make to argue against pre‐registration. We agree with 7 of the claims, but think that none of them justify delaying the encouragement and adoption of pre‐registration. Moreover, while the claim they make in their title is correct—pre‐registration is neither necessary nor sufficient for a credible science—this is also true of many our science's most valuable tools, such as random assignment. Indeed, both random assignment and pre‐registration lead to more credible research. Pre‐registration is a game changer. Abstract : This article is part of a Research Dialogue: Krishna (2021): https://doi.org/10.1002/jcpy.1211 Simmons et al. (2021): https://doi.org/10.1002/jcpy.1208 Pham & Oh (2021): https://doi.org/10.1002/jcpy.1209 Pham & Oh (2021): https://doi.org/10.1002/jcpy.1213